Вы находитесь на странице: 1из 6

a a

f (x, y) = x 2 e 3xy

f (2, 0) 4

f D f = R 2

f Im f = {z; 0 z < +∞}

f (x, y, z) = e zx 2 y 2

f (2, 1, 6) e

f D f = {(x, y, z)R 3 ; z x 2 + y 2 }

f Im f = {z; 1 z < +∞}

f (x, y) = 3

f (x, y) = 4x 2 + y 2 + 1

f (x, y) = 1 x y

f (x, y) = x 2 + y 2

 f (x, y) = xy f (x, y) = y − ln x f (x, y) = √ x + y f (x, y) = x − y 2

f (x, y, z) = x + 3y + 5z

f (x, y, z) = x 2 y 2 + z 2

(x,y)(5,2) (x 5 + 4x 3 y 5xy 2 ) = 2025

lim

(x,y)(0,0)

lim

(x,y)(0,0)

lim

(x,y)(0,0)

lim

xy cos y 3x 2 + y

2

2

x 4 + y 2

2x

y

2

x 2 + y 2

x

(x,y)(0,0) x 2 sin

lim

y

x = 0

(x,y)(0,0)

lim

x 2 y x 4 + y 4

2

lim

(x,y,z)(3,0,1)

e xy sin(πz/2) = 1

(x,y)(0,0)

lim

xy x 2 + y 2 = 0

(x,y)(0,0)

lim

x 2 + y 2 + 1 1 = 2

x 2 + y

2

(x,y,z)(0,0,0) xy + yz 2

lim

+

xz 2

x 2 + y 2 + z 4

(x,y)(0,0) e

lim

1+x+y

xy

= 1

(x,y)(0,0) 1 sin(x 2 + y 2 )

lim

x 2 + y 2

x

2

y 2 = 0

x 2 +

(h,k)(0,0) f (x + h, y + k) f (x, y) 2xh k

lim

(h, k)

f (x, y) = x 2 + y

0

(h,k)(0,0)

lim

f (h, k) (h, k)

f (x, y) =

x 3 x 2 + y 2

f (x, y) =

x 3y

   x 2 + y

   0,

2 ,

(x, y)

=

(0, 0)

(x, y) = (0, 0)

{(x, y) R 2 ; (x, y)

= (0, 0)}

f (x, y) =

R 2

xy 2

x 2 + y 2 ,

0,

(x, y)

= (0, 0)

(x, y) = (0, 0)

f (x, y) =

R 2

f (x, y) =

R 2

sin(x 2 + y 2 )

x 2 + y 2

1,

,

(x, y)

= (0, 0)

(x, y) = (0, 0)

x

3

x 2 + y 2 ,

0,

(x, y)

= (0, 0)

(x, y) = (0, 0)

f (x, y) = 5x 4 y 2 + xy 3 + 4

f x = 20x 3 y 2 + y 3 f y = 10x 4 y + 3xy 3

f (x, y) = cos xy

f x = y sin xy f y = x sin xy

f (x, y) = x x 2 3 + + y y 2 2

f x = x 4 + 3x 2 y 2 2xy 2 f y = 2x 2 y(1 x)

(x 2 + y 2 ) 2

(x 2 + y 2 ) 2

f (x, y) = xy

x+y

f x =

2y y) 2

(x +

f y =

2x

(x + y) 2

f (x, y) = x 2 ln(1 + x 2 + y 2 )

f x = 2x ln(1 + x 2 + y 2 ) +

2x 3

1 + x 2 + y 2

f (x, y) = xye xy

f y =

2x 2 y

1 + x 2 + y 2

f x = ye x y(1 + xy) f y = xe x y(1 + xy)

 f (x, y) = (4xy − 3y 3 ) 3 + 5x 2 y f x = 12y(4xy − 3y 3 ) 2 + 10xy f y = 3(4xy − 3y 3 ) 2 (4x − 9y 2 ) + 5x 2 f (x, y) = e −x 2 −y 2

f x =

2x

2y

e ( x 2 + y 2 ) f y = e ( x 2 + y 2 )

f (x, y) = (x 2 + y 2 ) ln(x 2 + y 2 )

f x = 2x[1 + ln(x 2 + y 2 )]

f y = 2y[1 + ln(x 2 + y 2 )]

 f (x, y, z) = xy 2 z 3 + 3yz f x = y 2 z 3 , f y = 2xyz 3 + 3z f z = 3xy 2 z 2 + 3y f (x, y, z) = ln(x + 2y + 3z)

f x =

1

2

x + 2y + 3z , f y x + 2y + 3z f z =

f (x, y, z, t) = xyz 2 tan(yt)

3

x + 2y + 3z

f x = yz 2 tan(yt), f y = xyz 2 t sec 2 (yt) + xz 2 tan(yt), f z = 2xyz tan(yt) f t = xy 2 z 2 sec 2 (yt)

ϕ : R R ϕ (1) = 4

g(x, y) = ϕ x

y

= 0

y

x ∂g (1, 1) = 4

y ∂g (1, 1) = 4

∂g

∂g

x x (x, y) + y y (x, y) = 0 (x, y) R 2 y

= 0

z = e y Φ(x y) Φ

∂z

∂x +

∂z

y = z

f (x, y) = x 3 y 2

2 f ∂x 2

=

6xy 2 , ∂y 2 f 2

f

= 2x 3 , xy = 6x 2 y

2

2

f

∂y∂x = 6x 2 y

z = e x 2 y 2

2 z

∂x 2

= 2e x 2 y 2 (1 + 2x 2 ),

2 z

∂y 2

z = ln(1 + x 2 + y 2 )

2 z

∂x 2

=

2 + 2y 2 2x 2

(1 + x 2 + y 2 ) 2 , ∂y 2 =

2 z

2 z

2 z

= 2e x 2 y 2 (2y 2 1), xy = 4xye x 2 y 2 yx = 4xye x 2 y 2

2 + 2x 2 2y 2

(1 + x 2 + y 2 ) 2 , ∂x∂y =

2 z

4xy

2 z

4xy

(1 + x 2 + y 2 ) 2 ∂y∂x = (1 + x 2 + y 2 ) 2

g(x, y)

= 4x 3 y 4 + y 3

2 g ∂x 2

=

24xy 4 ,

2 g ∂y 2

=

2

48x 3 y 2 + 6y, xy ∂ g = 48x 2 y 3

2

yx ∂ g = 48x 2 y 3

φ, ψ : R R

R u(x, y) = φ(x 2y) + ψ(x + 2y) (x, y) R 2

(x 0 , y 0 ) R 2

0

2 u

∂y 2

(x 0 , y 0 ) 4 ∂x 2 u 2 (x 0 , y 0 ),

u xx + u yy = 0

 u = x 2 − y 2 u = x 3 + 3xy 2 u = ln x 2 + y 2 u = e −x cos y − e −y cos x

u = 1 y 2 + z 2

u xx + u yy + u zz = 0

x 2 +

u tt = a 2 u xx

u = sin(kx) sin(akt)

u = (x at) 6 + (x + at) 6

t

a 2 t 2 x 2 u = sin(x at) + ln(x + at)

u =

 z = 4x 2 − y 2 + 2y (−1, 2, 4) z = −8x − 2y z = 4 − x 2 − 2y 2 (1, −1, 1) x − 2y + z = 4 z = y cos(x − y) (2, 2, 2) z = y

(1, 1, 2) (1, 1, 1)

f (x,

y) = xy

x + 6y 2z = 3

z = x 3 ln(y 2 )

dz = 3x 2 ln(y 2 )dx + 2x 3 dy

y

u = e t sin θ

du = e t sin θdt + e t cos θdθ

w = ln x 2 + y 2 + z 2 dw = xdx + ydy + zdz x 2 + y 2 + z 2

dz dt

z = x 2 y + xy 2 x = dz

dt

2 + t 4 y = 1 t 3

= 4(2xy + y 2 )t 3 3(x 2 + 2xy)t 2

z = sin x cos y x = πt y = t

dz

dt

=

π cos x cos y sin x sin y

2

t

w = xe y/z x = t 2 y = 1 t z = 1 + 2t

dw

dt

= e

y

z

2t x

z

2xy

z 2

dw

dt

z ∂s

∂z

∂t

z = x 2 + xy + y 2

x = s + t y = st

∂z

∂s

=

2x + y + xt + 2yt z ∂t

= 2x + y + xs + 2ys

z = arctan(2x + y) x = s 2 t y = s ln t

∂z

∂s =

 4st + ln t ∂z 1 + (2x + y) 2 ∂t =

2s 2 + s

t

1 + (2x + y) 2

z = e r cos θ r = st θ = s 2 + t 2

∂z

∂s

= e r s cos θ

t + t 2 sin θ z ∂t = e r t cos θ

s 2

s + t 2 sin θ

s 2

z = f (x, y) f

h(3) = 7 h (3) = 4 f x (2, 7) = 6 f y (2, 7) = 8 dz dt

x = g(t) y

= h(t) g(3) = 2 g (3) = 5

t = 3

62

z = x 2 + xy 3 x = uv 2 + w 3 y = u + ve w

85, 178, 54

∂z

∂z

∂z

∂u , ∂v , w

u = 2, v = 1, w = 0

R = ln(u 2 + v 2 + w 2 )

7 7

9 , 9

u = x + 2y v = 2x y w = 2xy R ∂x

, ∂R

∂y

x = y = 1

u = x 2 + yx x = pr cos θ y = pr sin θ z = p + r u ∂p

36, 24, 30

, ∂u , ∂u

∂θ

∂r

dy

dx

p = 2, r = 3, θ = 0

xy = 1 + x 2 y

dy

dx

=

4(xy) 3

2 y

x 2x 2 xy

cos(x y) = xe y

dy

dx =

sin(x y) y

e

sin(x y) xe y

∂z

∂x

∂z

∂y

x 2 + y 2 + z 2 = 3xyz

∂x = 3yz 2x

∂z

2z 3xy

∂y = 3xz 2y

∂z

2z 3xy

x z = arctan(yz)

z

∂x =

1 + y 2 z 2

∂z

z

1 + y + y 2 z 2

∂y = 1 + y + y 2 z 2

∂z

z = f (x, y) x = r cos θ y = r sin θ

∂z

∂z

∂x 2 + ∂y 2 = ∂z

∂r

2 +

z

∂r

1

r

2

θ

∂z

∂θ

2

z ∂r

= x cos θ + y sin θ z

∂θ

∂z

∂z

z = f (x y)

∂z

∂x + ∂y = 0

∂z

f (x, y) =

xy x 2 y 2

x 2 + y 2

0,

,

z = xye

x y x

= x r sin θ + y r cos θ

∂z

∂z

(x, y)

= (0, 0)

(x, y) = (0, 0)

3 z ∂x 3

+ y

3

∂y∂x 2 = 0

z

2 f

2 f

xy (0, 0) yx (0, 0)